PENGGUNAAN EKSTRAK KULIT KAYU GEMOR (Nothaphoebe coriacea K.) SEBAGAI LARVASIDA HAYATI TERHADAP TINGKAT MORTALITAS JENTIK NYAMUK Aedes aegypti SERTA DAMPAKNYA PADA KUALITAS AIR HUJAN - Pranata Dyah Susanti; Danang Biyatmoko; Dini Sofarini; Susilawati Susilawati (EnviroScienteae, 2013)
Gemor plants (Nothaphoebe coriacea K.) is the producer of one type of mainstay NTFP (Non-Timber Forest Products) in Kalimantan. Bark of gemor is potential to be used as a biological larvacide, especially against Aedes aegypti larvae which are the carriers of disease vectors of Dengue Hemorrhagic Fever (DHF). This study aimed to analyze the effect of bark extract concentration of gemor as a biological larvacide against: (1) the mortality rate of Aedes aegypti mosquito larvae, and (2) the physical and chemical quality of rainwater. The research method used was a completely randomized design (CRD) with 6 treatments and 5 replications. Treatment applied in this research was gemor bark extract concentration, namely: L0 (0 ppm), L1 (400 ppm), L2 (800 ppm), L3 (1,200 ppm), L4 (1,600 ppm), and L5 (2,000 ppm). Larvae used in this study were Aedes aegypti larvae in the third instar. The variables observed were the mortality rate of Aedes aegypti mosquito larvae and the rain water quality parameters, including pH and TDS. The results indicated that increasing concentrations of gemor bark extract significantly (p <0.05) increase the mortality rate of Aedes aegypti larvae. During 12 hours of observation, the percentage of larvae mortality at a concentration of 400 ppm (L1) was 42% and increased to 100% at a concentration of 2,000 ppm (L5), whereas in the control (L0) no  mortality was observed. Gemor bark extract may improve the rainwater pH between 0.02 to 0.04. TDS parameter value for the L0 treatment was 4 mg / l, while for the L1 it was 37.6 mg / l and increased to 806.2 mg / l for the L5 . Nonetheless, the value of TDS in the L5 concentration still meets the standards of Ministry of Health Decree No. 416/MENKES/PER/IX/1990 about the Terms and Water Quality Monitoring.